Two new flavonoids from Derris laxiflora Benth. (September 2017) - Chien, Shih-Chang; Chen, Chien-Chih; Wang, Sheng-Yang; Wu, Jyh-Horng; Shih, Chun-Ching; Chao, Louis Kuoping; Chao, Che-Yi; Chiu, His-Lin; Kuo, Yueh-Hsiung
Graphical abstract: Highlights: The The chemical constituents of Derris laxiflora Benth ., a member of the Leguminosae, were discussed. A new compound structure derriscoumaronochromone was elucidated by analysis of spectroscopic data. A new compound structure cis -3, 4′-dihydroxy-5, 7-dimethoxyflavan was elucidated by analysis of spectroscopic data. Abstract: Two new compounds, derriscoumaronochromone (1 ) and cis -3, 4′-dihydroxy- 5, 7-dimethoxyflavan (2 ), as well as trans -4'- O -methylcatechin (3 ) were isolated from Derris laxiflora, The structures of these compounds were determined by analysis of their spectroscopic data.